(untitled) (Research, Society and Development, 2023)
Introduction: Head and neck cancer, estimated at 118,650 new cases in Brazil for 2023-2025, is influenced by factors such as smoking, alcohol consumption, and HPV, primarily affecting men. Symptoms vary depending on the tumor’s location. Objective: This study aims to assess the impact of radiotherapy on mucositis and the nutritional status of head and neck cancer patients, aiming to improve their quality of life and treatment efficacy. Methodology: A scoping review was conducted following the PRISMA-ScR protocol, seeking studies from 2018 to 2023 in LILACS, PUBMED, MEDLINE, and SciELO, resulting in the selection of 9 relevant articles. Results: The reviewed studies identified nutritional strategies and interventions such as oral gel and photobiomodulation that have a positive impact on patients’ mucositis and nutritional status. Conclusion: The significance of early nutritional intervention and multidisciplinary approaches in enhancing the quality of life for head and neck cancer patients undergoing radiotherapy is emphasized.